Antimicrobial chemical constituents from abrus precatorius - Lorena, Giancarlo S. (Animo Repository, 2011)
Chemical constituents from air-dried fruit (without seeds), seeds, and peduncle of the plant, Abrus precatorius were extracted using dichloromethane (DCM). The extracts were then separated into their different components using silica gel chromatography. The DCM extracts of the empty pods afforded a triterpene abrusogenin (APO3), a monoglyceride (APO4) and a triglyceride (APO8). The DCM extract of the seeds yielded a mixture (APS2) of stigmasterol and sitosterol in a 4:1 ratio respectively and a triglyceride (APS1). The DCM extracts of the peduncle on the other hand, afforded a triglyceride (APP2). The structures of APO3 and APO4 were elucidated using extensive 1D and 2D NMR spectroscopy. The mixture APS2, and triglycerides APO8, APS1 and APP2 were identified through comparison of their 1H NMR and 13C NMR data with those reported in literature. Antimicrobial test using the compounds isolated from the fruit (without seeds) APO3, APO4 and APO8 indicated that these compounds were active against gram positive bacteria: Stapylococcus aureus, Bacillus subtilis, gram negative bacteria: Pseudomonas aeruginosa and fungi: Candida albicans, and Trichophyton mentagrophytes.